Hout in sy brood! lets oor Calvyn se Bybelgebruik - Schulze, L.F. (Hervormde teologiese studies, 1991)
Wood in his bread! Something about Calvin’s use of Scriptures In his discussion of the Lord’s Supper Calvin refers in one instance (Inst 4.17.15) to Jeremia 11:19. In this article, attention is given to Calvin’s representation of a part of the text. Says Calvin: ‘The prophet complains that wood was placed in his bread, intimating that by the cruelty of his enemies his bread was infected with bitterness....’ In the Revised Standerd Version Jeremia 11:19b reads: ‘Come, let us destroy the tree with its fruit.’ This discrepancy is explained by discussing the difficulties in translating the Hebrew, and some conjectures that have been proposed to overcome these difficulties.